2021
DOI: 10.1177/1553350621996972
|View full text |Cite
|
Sign up to set email alerts
|

Super-Selective Intra-Arterial Indocyanine Green Administration for Near-Infrared Fluorescence-Based Positive Staining of Hepatic Segmentation: A Feasibility Study

Abstract: Background. Despite the increasing number of laparoscopic hepatic procedures for the resection of hepatocellular carcinoma (HCC), intraoperative tumor localization and demarcation remains challenging in comparison to open surgery. In this study, we evaluated the feasibility of positive liver segment staining through the super-selective intra-arterial indocyanine green (ICG) administration. Methods. Eight patients presenting with a single HCC underwent an interventional vascular procedure followed by laparoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…With the guidance of DSA examination, Grade 4 (or higher) hepatic arteries could be reached; thus, the liver watershed (or sub-segment) staining could be achieved via injection of the ICG through the aimed hepatic artery. Li et al have proved that intra-arterial ICG injection provided a real-time image-guided intraoperative demarcation of targeted liver Couinaud segments (20). However, the liver watershed (or sub-segment) staining via the hepatic artery has not been explored in that study.…”
Section: Discussionmentioning
confidence: 96%
“…With the guidance of DSA examination, Grade 4 (or higher) hepatic arteries could be reached; thus, the liver watershed (or sub-segment) staining could be achieved via injection of the ICG through the aimed hepatic artery. Li et al have proved that intra-arterial ICG injection provided a real-time image-guided intraoperative demarcation of targeted liver Couinaud segments (20). However, the liver watershed (or sub-segment) staining via the hepatic artery has not been explored in that study.…”
Section: Discussionmentioning
confidence: 96%
“…Due to selective uptake by the liver and unique metabolic characteristics, ICG is particularly suitable for HCC resection. For instance, Wang et al reported the IVR-aided selective intra-arterial injection technique for ICG fluorescence-based positive staining of hepatic segmentation during laparoscopic surgery, verifying the feasibility of real-time imaging-guided demarcation and definition of the resection line for targeted liver segments . Likewise, the combined utilization of ICG fluorescence imaging and IVR for the determination of liver segments during laparoscopic HCC resection was investigated by Yamaue’s group .…”
Section: Interventional Fluorescence Imaging In Preclinical and Clini...mentioning
confidence: 97%
“…For navigation during anatomic hepatectomy (AR), the most widely used field of ICG, it mainly relies on “positive” or “negative” staining techniques to achieve fluorescence visualization of liver segments or lobes via portal vein 5 , 6 . Currently, various combined intervention techniques are also utilized to achieve fluorescence visualization, such as the “positive dyeing” technique via the hepatic artery 7 10 . Additionally, in the surgical treatment of intrahepatic bile duct calculi, some scholars have utilized the principle of ICG excretion through a biliary duct to accurately locate the scope of atrophic liver, intrahepatic calculi, and diseased bile duct, 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%